Investigation of upper limb prosthesis functionality using quantitative design tools - Chua, Chung Han (2022)
Upper limb prostheses offer those with limb loss a solution to restore some of their lost functionality by allowing them to participate in bilateral tasks, especially those required for daily living. Whilst there is a wide range of upper limb prostheses available, there remain high device rejection rates. Low functionality and discomfort are major factors in prosthesis rejection, which had been identified as challenges more than 60 years ago. These issues have not been effectively addressed due the lack of design tools for engineers and clinicians. Upper limb prostheses have seen greater technological advances than the methods to evaluate them effectively, which has resulted in over-engineered designs which do not meet the needs of their user.